P-B22 Recurrence of cervical intraepithelial lesions after Thermo-coagulation in HIV-positive and HIV-negative Nigerian Women. (January 2016) - Oga, Emmanuel; Brown, Jessica; Brown, Clayton; Dareng, Eileen; Olaniyan, Olayinka; Offiong, Richard; Adekanmbi, Victor; Odutola, Michael; Obende, Kayode; Stephen, Adewole; Peter, Achara; Dakum, Patrick; et al.
Abstract : Background: The burden of cervical cancer remains huge globally, more so in sub-Saharan Africa. Effectiveness of screening, rates of recurrence following treatment and factors driving these in Africans have not been sufficiently studied. The purpose of this study therefore was to investigate factors associated with recurrence of cervical intraepithelial lesions following Thermo-coagulation in HIV-positive and HIV-negative Nigerian women using Visual Inspection with Acetic Acid (VIA) or Lugol's Iodine (VILI) for diagnosis. Methods: A retrospective cohort study was conducted, recruiting participants from the cervical cancer "see and treat" program of IHVN. Data from 6 sites collected over a 4-year period was used. Inclusion criteria were: age ≥18 years, baseline HIV status known, VIA or VILI positive and thermo-coagulation done. Logistic regression was performed to examine the proportion of women who returned for their scheduled follow-up, those with recurrence and factors associated with recurrence. Student's t test was used to compare continuous variables between HIV-positive and HIV-negative women while Fisher's exact test was performed for categorical variables. Results: Out of 177 women included in study, 67.8% (120/177) were HIV-positive and 32.2% (57/177) were HIV-negative. Recurrence occurred in 16.4% (29/177) of participants; this was 18.3% (22/120) in HIV-positive women compared to 12.3% (7/57) in HIV-negative women but this difference was not statistically significant ( P -value 0.31). Women aged ≥30 years were much less likely to develop recurrence, adjusted OR = 0.34 (95% CI: 0.13 to 0.92). Among HIV-positive women, CD4 count <200 cells per cubic millimeter was associated with recurrence, adjusted OR = 5.47 (95% CI: 1.24 to 24.18). Conclusions: Recurrence of VIA or VILI positive lesions after Thermo-coagulation occurs in a significant proportion of women. HIV-positive women with low CD4 counts are at increased risk of recurrent lesions and may be related to immunosuppression.